PENGARUH MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA AUGMENTED REALITY TERHADAP PENINGKATAN KEMAMPUAN BERPIKIR KRITIS IPA SISWA SEKOLAH DASAR - Ica Nurlaela; Afridha Laily Alindra; Wina Mustikaati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Critical thinking skills are an important competency of the 21st century, but are still low in science learning in elementary schools. One of the efforts to improve is through the application of the Problem Based Learning (PBL) model assisted by Augmented Reality media which encourages active student involvement. This study aims to: (1) Determine the increase in students' critical thinking skills in science in elementary schools who receive the application of the Problem Based Learning (PBL) model assisted by Augmented Reality media is better than students who receive the application of the Discovery Learning model assisted by PowerPoint, and (2) Determine the effect of increasing students' critical thinking skills in science in elementary schools through the application of the Problem Based Learning (PBL) model assisted by Augmented Reality media. This study uses a quasi-experimental method with a non-equivalent control group design. The subjects were students of grades IVA and IVB of SDN Purwamekar on the material of plant body parts. Data collection techniques used pretest, posttest, and documentation. The results of the study showed: (1) The increase in students' critical thinking skills with the Problem Based Learning (PBL) model assisted by Augmented Reality was higher, which was 77.31%, and (2) There was an effect of increasing students' critical thinking skills in science learning in elementary schools through the application of the PBL model assisted by Augmented Reality media of 54.70%. Thus, the application of the Problem Based Learning (PBL) model assisted by Augmented Reality is effective in improving the critical thinking skills of elementary school students in science.